Android smartphones for seniors for dummies - Collier, Marsha (For Dummies, 2022)
The quickest and easiest way to outsmart your Android smartphone Android smartphones, like the Samsung Galaxy and Google Pixel models, offer great ways to simplify and enhance your life. From easy ways to stay in touch with your friends and family to helpful reminders for everyday tasks, Android phones can keep you connected and current at all times. Sometimes, though, the learning curve can seem a little steep. But it doesn't have to! Android Phones For Seniors For Dummies is your one-stop guide to discovering the essentials on how to take charge of your Android-powered phone. It skips the techspeak and confusing jargon to deliver key information in a straightforward and reader-friendly way. With this book, you'll learn to: Navigate your way around your smartphone so you can easily open and close apps, access info, and see photos Read your email and messages so you can stay in touch with the important people in your life Secure your phone so you can be assured that you, and only you, can access the sensitive data on it Printed using larger-print type and accompanied by full-color pictures that show you how to apply the step-by-step instructions, this easy handbook is the only resource you'll need to make the most of your Android phone.